Levantamento fitossociológico em pastagens - Inoue, M. H.; Silva, B. E.; Pereira, K. M.; Santana, D. C. [UNESP]; Conciani, P. A.; Sztoltz, C. L. (FapUNIFESP (SciELO), 2012)
Objective of this study was to identify the weed community in areas of pasture. The phyto-sociological survey was conducted during November and December, 2009 in three regions: two located in Tangará da Serra-MT (region A = areas surrounding the town; and region B = areas in the Antonio Conselheiro Settlement and one area in Barra of the Bugres-MT (region C). Five properties were analyzed in each region, each containing 10 plots of 25 m 2. The weed species were counted and identified in the plots. Data were analyzed by calculating density, frequency, abundance, relative density, relative frequency, relative abundance, importance value index (IVI), and similarity index. Thirty-eight weed species were identified, distributed among 18 families, with Asteraceae (7), Fabaceae (6), Arecaceae (3), Euforbiaceae (3) and Poaceae (3) being the most representative in number of species. The species most frequently found were: region A - Sida spp. (IVI: 127.93) and Eragrostis plana (IVI: 42.18); region B - Eragrostis plana (IVI: 54.78), Mimosa wedelliana (IVI: 52.39), and Sida spp. (IVI: 50.30); and region C - Sida spp. (IVI: 73.92), and Mimosa wedelliana (IVI: 26.55). A significant similarity was found between regions A and B (52.63%) and between regions B and C (50.98%).
Phyto-sociological assessment of pasture
Keywords: Brachiaria spp; Importance value index; Similarity; Weeds